Teosofi Islam: Jalan Spiritual untuk Menyatukan Syariat dan Akhlak di Era Modern: Jalan Spiritual untuk Menyatukan Syariat dan Akhlak di Era Modern - andini, nur ania (Maliki Interdisciplinary Journal, 2025)
This study explores Islamic theosophy as an integrative framework combining normative sharia and ethical values in contemporary contexts. The theosophical approach synthesizes legal-formal aspects with spiritual-emotional dimensions, rooted in Sufism and Islamic philosophy emphasizing ma'rifah (gnosis) and divine proximity. As an alternative paradigm, Islamic theosophy bridges external legality and internal moral awareness through transformative spiritual education. Using philosophical analysis, the research maps its role in harmonizing religious law and ethics, as well as developing inclusive, humanistic religious education and practice